2010
DOI: 10.1073/pnas.0912228107
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Wnt7b is critical for kidney repair and regeneration

Abstract: Macrophages are required for tissue homeostasis through their role in regulation of the immune response and the resolution of injury. Here we show, using the kidney as a model, that the Wnt pathway ligand Wnt7b is produced by macrophages to stimulate repair and regeneration. When macrophages are inducibly ablated from the injured kidney, the canonical Wnt pathway response in kidney epithelial cells is reduced. Furthermore, when Wnt7b is somatically deleted in macrophages, repair of inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
374
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(402 citation statements)
references
References 37 publications
(38 reference statements)
22
374
2
1
Order By: Relevance
“…Activation of WNT signalling alone induced fibrogenic factors in HRPTC It has been reported that HRPTC are the primary cells that respond to WNT activation after kidney injury [25]. As hyperglycaemia and HNE can trigger multiple signalling pathways [22,[26][27][28][29], in order to confirm the direct effect of WNT activation on renal fibrogenesis in diabetic nephropathy, primary HRPTC were exposed to WNT3A-conditioned medium (WCM); plain L cell conditioned medium (LCM) was used as a control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of WNT signalling alone induced fibrogenic factors in HRPTC It has been reported that HRPTC are the primary cells that respond to WNT activation after kidney injury [25]. As hyperglycaemia and HNE can trigger multiple signalling pathways [22,[26][27][28][29], in order to confirm the direct effect of WNT activation on renal fibrogenesis in diabetic nephropathy, primary HRPTC were exposed to WNT3A-conditioned medium (WCM); plain L cell conditioned medium (LCM) was used as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Values are expressed as the percentages of the control (Con) values (mean±SD, n=3); *p<0.05. e-h HRPTC were treated with HNE (10 μmol/l) for 6 h. Cytosolic (e, f) and nuclear (g, h) β-catenin levels were measured by western blot analysis using the cytosolic and nuclear fractions, quantified by densitometry from three independent experiments, and normalised to glyceraldehyde-3-phosphate dehydrogenase (GAPDH) levels or histone-3 levels, respectively. Values are expressed as percentages of control values (mean±SD, n=3); *p<0.05 and **p<0.01 been shown to induce overexpression of Wnt1, Wnt2, Wnt2b, Wnt3, Wnt3a, Wnt8a, Wnt16, Fzd3, Fzd4, Fzd9 and Fzd10 gene expression in kidney [14,25], suggesting that the activation of the WNT signalling pathway may be a common pathogenic mechanism for some kidney diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In some normal adult tissues, Wnt / β -catenin signalling activity has been shown to mainly reside in stem or progenitor cells and to increase upon injury 17,18,49 . Interestingly, stem or progenitor cells are suggested to be fusion partners of transplanted bone marrowderived cells in tissue regeneration, at least in the intestine 3 .…”
Section: Discussionmentioning
confidence: 99%
“…5,24,[33][34][35] Separately primary proximal tubular epithelial cells were selectively cultured as described. 33,35 Isolation and Culture of Primary Kidney Pericyte…”
Section: Isolation and Culture Of Cells From Kidneymentioning
confidence: 99%